Lembaga Keuangan Mikro Masyarakat (LKMM) Dalam Pemberdayaan Perekonomian Masyarakat Desa - Dhevin M.Q Agus Puspita W (INAIFAS Press, 2020)
Community microfinance institutions are tools or platforms for empowering the people's potential based on the people's economic capacity through a togetherness approach as an integral part in strengthening the national economy. In the context of rural community development, community classifications can be grouped into three types, namely self-help villages, self-help and self-sufficiency villages. The existence of a community microfinance institution (LKMM) for community economic empowerment is a very important and need to be developed. In implementing this institution there are several things that need to be considered, namely: First, the principles and objectives of empowerment include: 1) the growth of independence, togetherness, and entrepreneurship. 2) the realization of public policies that are transparent, accountable and fair. 3) business development based on regional potential and market oriented in accordance with business competencies, micro, small and medium enterprises. 4) increasing the competitiveness of micro, small and medium businesses. 5) integrated planning, implementation and control. Second, the process and effort of empowerment includes creating an atmosphere or climate that enables the potential of the community to develop optimally, strengthen, protect, support and maintain. While the existence of LKMM in the community's economy, among others, is able to create a conducive business climate, there is capital assistance that does not burden small and medium business actors in its use, there is business protection, there is partnership development, there is training for small and medium business actors as well as the association and cooperation between the government and the business community in the village community.